2007
DOI: 10.1016/j.cell.2007.03.049
|View full text |Cite
|
Sign up to set email alerts
|

Extending the Host Range of Listeria monocytogenes by Rational Protein Design

Abstract: In causing disease, pathogens outmaneuver host defenses through a dedicated arsenal of virulence determinants that specifically bind or modify individual host molecules. This dedication limits the intruder to a defined range of hosts. Newly emerging diseases mostly involve existing pathogens whose arsenal has been altered to allow them to infect previously inaccessible hosts. We have emulated this chance occurrence by extending the host range accessible to the human pathogen Listeria monocytogenes by the intes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
264
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 195 publications
(278 citation statements)
references
References 53 publications
13
264
1
Order By: Relevance
“…This suggests that, in models permissive to both InlA and InlB, InlB-requirement for Lm invasion of Peyer's patch There are apparently conflicting data regarding the role of InlB in the crossing of intestinal barrier: whereas we have repeatedly found no role for InlB in Lm crossing of the intestinal barrier in in vivo models permissive to both InlA-Ecad and InlB-c-Met interactions (Khelef et al, 2006;Disson et al, 2008), it has been reported by others that InlB accelerates invasion at villous tips in an experimental model using murinized InlA (Pentecost et al, 2010) and plays a role at the Peyer's patch level in WT mice (Chiba et al, 2011). Here, we have confirmed these results and revisited their interpretations in light of our new investigations: we compared the infection of murinized InlA (InlA m ) expressing Lm (Wollert et al, 2007) in WT mice (Pentecost et al, 2010) and the infection of WT Lm in KIE16P mice expressing humanized mEcad (Disson et al, 2008) at the villous tip level. Importantly, we have recently demonstrated that InlA m confers to Lm the ability to target both Ecad and Ncad, the latter being accessible on the luminal side of villous M cells (Tsai et al, 2013).…”
Section: Discussionsupporting
confidence: 72%
“…This suggests that, in models permissive to both InlA and InlB, InlB-requirement for Lm invasion of Peyer's patch There are apparently conflicting data regarding the role of InlB in the crossing of intestinal barrier: whereas we have repeatedly found no role for InlB in Lm crossing of the intestinal barrier in in vivo models permissive to both InlA-Ecad and InlB-c-Met interactions (Khelef et al, 2006;Disson et al, 2008), it has been reported by others that InlB accelerates invasion at villous tips in an experimental model using murinized InlA (Pentecost et al, 2010) and plays a role at the Peyer's patch level in WT mice (Chiba et al, 2011). Here, we have confirmed these results and revisited their interpretations in light of our new investigations: we compared the infection of murinized InlA (InlA m ) expressing Lm (Wollert et al, 2007) in WT mice (Pentecost et al, 2010) and the infection of WT Lm in KIE16P mice expressing humanized mEcad (Disson et al, 2008) at the villous tip level. Importantly, we have recently demonstrated that InlA m confers to Lm the ability to target both Ecad and Ncad, the latter being accessible on the luminal side of villous M cells (Tsai et al, 2013).…”
Section: Discussionsupporting
confidence: 72%
“…T he route or site of inoculation has been shown to significantly influence disease outcome in numerous models of infection, including Leishmania (1-9), Toxoplasma (10), Plasmodium (11), Listeria (12)(13)(14), Borrelia (15), and influenza virus (16,17) infections. Vaccination by different routes has also been shown to influence the efficacy of vaccines against parasitic, bacterial, and viral infections, as well as cancer (3,(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28).…”
mentioning
confidence: 99%
“…The Internalin A mutant recombinant strain of L. monocytogenes provides an excellent means to model human L. monocytogenes infection in mice, because the modified Internalin A binds mouse E-cadherin with similar efficiency as the human counterpart (11). Using this model, we previously found the existence of L. monocytogenes-specific protective memory like γδ T-cell population in mice (12).…”
Section: Discussionmentioning
confidence: 99%